Regulation of intracellular signaling and function by caveolin. Issue 9 (22nd May 2014) - Fridolfsson, Heidi N.; Roth, David M.; Insel, Paul A.; Patel, Hemal H.
Abstract : Caveolae, flask‐like invaginations of the plasma membrane, were discovered nearly 60 years ago. Originally regarded as fixation artifacts of electron microscopy, the functional role for these structures has taken decades to unravel. The discovery of the caveolin protein in 1992 (by the late Richard G.W. Anderson) accelerated progress in defining the contribution of caveolae to cellular physiology and pathophysiology. The three isoforms of caveolin (caveolin‐1, ‐2, and ‐3) are caveolae‐resident structural and scaffolding proteins that are critical for the formation of caveolae and their localization of signaling entities. A PubMed search for "caveolae" reveals 280 publications from their discovery in the 1950s to the early 1990s, whereas a search for "caveolae or caveolin" after 1990, identifies 7000 entries. Most work on the regulation of biological responses by caveolae and caveolin since 1990 has focused on caveolae as plasma membrane microdomains and the function of caveolin proteins at the plasma membrane. By contrast, our recent work and that of others has explored the localization of caveolins in multiple cellular membrane compartments and in the regulation of intracellular signaling. Cellular organelles that contain caveolin include mitochondria, nuclei and the endoplasmic reticulum. Such intracellular localization allows for a complexity of responses to extracellular stimuli by caveolin and the possibility of novel organelle‐targeted therapeutics. This review focuses on the impact of intracellular localization of caveolin on signal transduction and cell regulation.—Fridolfsson, H. N., Roth, D. M., Insel, P. A., Patel, H. H. Regulation of intracellular signaling and function by caveolin. FASEB J. 28, 3823‐3831 (2014). www.fasebj.org